Sosialisasi Shorinji Kempo pada Pemuda Karang Taruna Desa Pulubala Kecamatan Pulubala Kabupaten Gorontalo - Mile, Sarjan (Jambura Arena Pengabdian, 2023)
This service aims to promote the martial arts sport of Shorinji Kempo, especially among Youth Youth Organizations, which are held in Pulubala Village, Pulubala District, Gorontalo Regency. As well as to encourage efforts to increase the development of Shorinji Kempo martial arts achievements among Youth Youth Organizations in Pulubala Village, Pulubala District, Gorontalo Regency. The method used in this service is the lecture method, question and answer, and demonstration. It is hoped that the results of the Socialization of the Shorinji Kempo Self-Defense Sports can be developed by the Karang Taruna Youth of Pulubala Village, Pulubala District, Gorontalo Regency through Achievement Development for Karang Taruna Youth, because this martial arts sport is a martial sport that is most in demand and popular with people, starting with children: children, youth, and parents.